Shrinkage curve and its role in estimating unsaturated shear strength and permeability functions for a weathered soil - Tran Thi Phuong, An; Fredlund, Delwyn G.; Do Quang, Thien (Vietnam Journal of Earth Sciences, 2026)
The soil shrinkage curve (SC) and the shrinkage limit are important for assessing the impact of volume change as soil dries. The SC is used to calculate the degree of saturation from the soil-water characteristic curve (S-SWCC) and is subsequently used to estimate other unsaturated soil property functions, such as shear strength and hydraulic conductivity. The present research aims are to: (1) identify the most appropriate parameters for the estimation for the SC without conducting a SC test, (2) investigate the effect of the initial compaction degree, characterized by void ratio and dry density, on the SC, and (3) emphasize the role of SC as it relates to the unsaturated shear strength and permeability functions. To achieve these objectives, the SC and SWCC tests were conducted on a weathered soil sample collected from a natural landslide slope along Route 74 connecting A Luoi and Nam Dong in Hue, Vietnam. The findings show that the SC can be predicted using empirical equations, thereby negating the need for direct SC testing. Unsaturated soil functions can be estimated from the SC and S-SWCC.